New Usage of a Fluorometric Method to Assay Antioxidant Activity in Plant Extracts: Fluorometric assay for antioxidant activity assessment - Soheila Moein; Mahmood Reza Moein (Iranian Journal of Pharmaceutical Sciences, 2012)
In the present study, an oxidative conversion of non-fluorescent dichlorofluoroscein (LDCF) to fluorescent dichlorofluoroscein (DCF) was used for detection of antioxidant properties of plant extracts. The rate of the reaction was followed by monitoring the formation of DCF as a function of time. The antioxidant assay was carried out for different concentrations of gallic acid, Salvia mirzayanii, Rech. f & Esfand Phlomis persica Boiss crude extracts and their fractions obtained by thin layer chromatography (TLC). The results showed that the fluorometric method could be used to detect lower concentrations of antioxidants. Thus, we were able to identify the antioxidant activity of five fractions obtained by TLC of Salvia mirzayanii extract and four fractions in TLC of Phlomis persica extract. This method is a good candidate to be used in high throughput screening.